2022
DOI: 10.3390/molecules27030840
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Beverage: A New Strategy for the Synthesis of Polymethacrylates via ATRP

Abstract: Coffee, the most popular beverage in the 21st century society, was tested as a reaction environment for activators regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP) without an additional reducing agent. Two blends were selected: pure Arabica beans and a proportional blend of Arabica and Robusta beans. The use of the solution received from the mixture with Robusta obtained a high molecular weight polymer product in a short time while maintaining a controlled structure of the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…65,66 In many cases, the occurring side reactions decrease the control over the process, resulting in high dispersity 16,49 and low initiation efficiency. [67][68][69] However, some techniques are progressing to overcome those setbacks to create more environmentally friendly processes, able to be implemented on a larger scale. An excellent example would be employing oxygen scavengers such as glucose oxidase 36,70 to conduct syntheses in air conditions, 9,27,43,48,[70][71][72][73][74][75] using catalysts characterized by high activity, e.g.…”
Section: Monika Flejszarmentioning
confidence: 99%
See 2 more Smart Citations
“…65,66 In many cases, the occurring side reactions decrease the control over the process, resulting in high dispersity 16,49 and low initiation efficiency. [67][68][69] However, some techniques are progressing to overcome those setbacks to create more environmentally friendly processes, able to be implemented on a larger scale. An excellent example would be employing oxygen scavengers such as glucose oxidase 36,70 to conduct syntheses in air conditions, 9,27,43,48,[70][71][72][73][74][75] using catalysts characterized by high activity, e.g.…”
Section: Monika Flejszarmentioning
confidence: 99%
“…Additionally, in the last 20 years, it was revealed that many compounds might play a dual role in the polymerization mechanism. For example N-phenylphenothiazine as photocatalyst and oxygen scavenger, 73 2-(dimethylamino)ethyl methacrylate as the monomer and internal reducing factor, 11,69 nitrogen-based ligands as reducing factors 72,[104][105][106] or non-conventional solvents containing various types of 'impurities' playing important roles in the RDRP mechanism (Fig. 2).…”
Section: Monika Flejszarmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of using alcoholic beverages including flavored Bison Grass Vodka as a reaction medium has been successfully demonstrated for the blue‐light‐assisted synthesis of PDMAEMA brushes, 26 but still no such solution has been presented for non‐water miscible monomers. For example, an attempt was made to synthesize P n BA in coffee extract‐based miniemulsion, however the synthesized polymers were characterized by a wide molecular weight distribution ( Ð = 3.07), which suggested an uncontrolled polymerization 27 . Herein, an environmentally friendly synthetic system using functional wine‐based miniemulsion as a reaction medium for the low ppm ATRP (~300 ppm by wt of Cu II /tris(2‐pyridylmethyl)amine [TPMA]) of hydrophobic (meth)acrylates is presented for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an attempt was made to synthesize PnBA in coffee extract-based miniemulsion, however the synthesized polymers were characterized by a wide molecular weight distribution (Ð = 3.07), which suggested an uncontrolled polymerization. 27 Herein, an environmentally friendly synthetic system using functional winebased miniemulsion as a reaction medium for the low ppm ATRP ($300 ppm by wt of Cu II /tris(2-pyridylmethyl)amine [TPMA]) of hydrophobic (meth)acrylates is presented for the first time.…”
Section: Introductionmentioning
confidence: 99%